Strategi Adaptasi Mahasiswa Bekerja (Studi Atas Mahasiswa Program Studi Pendidikan Sosiologi FKIP ULM) - Aspi Raehan; Yuli Apriati (Universitas Lambung Mangkurat, 2023)
Students who are supposed to focus on getting an education, have to struggle more because they are working at the same time. This certainly requires a process of adjustment or adaptation of the individual/group in a new environment. This study uses a qualitative method. The data source was selected by purposive sampling, with four informants. Data was collected using observation techniques, interviews and documentation. Analysis of research results using data reduction, data presentation and data verification. The results of the study show that: (1) The way students of the Sociology Education Study Program FKIP ULM work in overcoming obstacles from the environment, both the work environment and the campus environment. There are two ways to overcome obstacles in the work environment, namely coordination of working hours and additional work. There are four ways to overcome obstacles in the campus environment, namely trying to attend lectures, trying to do assignments, eliminating fatigue and doing college assignments after work. (2) Environmental adjustment in the workplace of students of the Sociology Education Study Program FKIP ULM who work using the concept of self-adjustment in work or the term is work adjustment which consists of adjustments to job selection, adjustment to work, stability of work choices and success of environmental adjustment at workplace.